Efforts to Improve Language Skills through the Use of Letter Cards in Children at RA Kusuma Mulia I - Anistiyani; Kurniawati, Rojiyah (DEEP LEARNING: Journal of Educational Research, 2025)
Language is a fundamental aspect in early childhood development because it plays an important role in the process of communication, thinking, and personality formation. This study aims to: (1) develop children's language skills through letter card media, and (2) create enjoyable learning by utilizing this media in Group B RA Kusuma Mulia I. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles with 10 students as research subjects in Bergas District, Semarang Regency. The data analysis technique used is descriptive percentage to assess learning outcomes and descriptive qualitative to observe children's activities during learning. The results of the study show that the use of letter card media can significantly improve children's language skills. Children are more enthusiastic, active, and easily understand letters and words learned through interesting concrete media. Thus, letter card media is proven to be effective as an alternative language learning strategy for early childhood. This study recommends that teachers utilize letter card media creatively in learning activities, so that children can learn in a more interactive, interesting, and enjoyable atmosphere.